PENINGKATAN PENINGKATAN LITERASI DIGITAL MASYARAKAT MELALUI PENDEKATAN PARTISIPATIF PADA PROGRAM KKM TEMATIK STKIP BINA MUTIARA DI DESA KALIBUNDER: Pelaksanaan Program KKM Tematik dalam Meningkatkan Literasi Digital - Asep Sahrul Gunawan; Nurlaelasari, Eka; Euis Maelani; Muhammad Lutfi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital literacy skills in order to use technology wisely, safely, and responsibly. However, many students still utilize digital technology primarily for communication, entertainment, and simple information retrieval without fully understanding digital ethics, personal data security, or the educational potential of Artificial Intelligence (AI). Therefore, this community service program aimed to improve students' digital literacy through a participatory approach. The program was conducted as part of the Thematic Community Service Program (Kuliah Kerja Mahasiswa/KKM) of STKIP Bina Mutiara on July 24 and 27, 2026, at SMAN 1 Kalibunder and MTs Nurul Islam Kalibunder, Kalibunder Village, Kalibunder District, Sukabumi Regency, Indonesia. This study employed a qualitative approach using participatory and educational strategies consisting of needs assessment, planning, socialization, workshops, hands-on practice, mentoring, and evaluation. The training materials covered digital literacy, the application of Artificial Intelligence (AI) in education, ethical use of AI, personal data protection, digital privacy, and strategies for identifying misinformation (hoaxes). The results demonstrated an improvement in participants' understanding of digital literacy concepts, the use of AI as a learning support tool, ethical AI practices, and the importance of protecting personal data and digital privacy. In addition, participants exhibited more critical attitudes in evaluating online information, became more cautious in using digital media, and showed greater confidence in utilizing AI-based applications to support their learning activities. The findings indicate that the participatory approach was effective in enhancing students' digital literacy competencies and has the potential to serve as a sustainable community service model for fostering digitally literate, ethical, and technology-adaptive learners.